Familial Immune Thrombocytopenia Associated With a Novel Variant in IKZF1 - Sriaroon, Panida; Chang, Yenhui; Ujhazi, Boglarka; Csomos, Krisztian; Joshi, Hemant R.; Zhou, Qin; Close, Devin W.; Walter, Jolan E.; Kumánovics, Attila (Frontiers in Pediatrics, 2019)
IKAROS haploinsufficiency can present with infections, autoimmunity, leukemia, or patients can be clinically asymptomatic. Here we present a case of familial immune thrombocytopenia (ITP) that was subsequently found to have IKAROS deficiency. Our patient first presented with treatment-refractory ITP at age 4 years. His mother also had ITP and required splenectomy. Familial ITP is rare and a concern was raised for possible underlying primary immunodeficiency disease. Immune evaluation revealed low serum immunoglobulin levels and vaccine titers. Genetic testing identified a novel variant of IKZF1. IKAROS is a hematopoietic zinc-finger transcription factor encoded by the IKZF1 gene and can directly bind to DNA. The DNA-binding portion of IKAROS is formed by four zinc-finger domains. We show that the IKZF1 variant (p.His195Arg) identified in our patient alters a completely conserved histidine residue required for the folding of the third zinc-finger of IKAROS protein, leading to a loss of characteristic DNA-binding pattern. Differentiating primary and secondary ITP is critical, as it can alter management. Genetic testing can help to establish the underlying diagnosis and monitor for potential complications, such as the increased risk of developing aberrant hematopoiesis, leukemia, and age-related decrease in humoral immunity seen in patients with IKAROS deficiency. Our family study underscores that, after infections, ITP is the second most common clinical manifestation of IKAROS haploinsufficiency.